MenAfriNet: A Network Supporting Case-Based Meningitis Surveillance and Vaccine Evaluation in the Meningitis Belt of Africa. (31st October 2019) - Patel, Jaymin C; Soeters, Heidi M; Diallo, Alpha Oumar; Bicaba, Brice W; Kadadé, Goumbi; Dembélé, Assétou Y; Acyl, Mahamat A; Nikiema, Christelle; Lingani, Clement; Hatcher, Cynthia; Acosta, Anna M; Thomas, Jennifer D; et al.
Abstract: Meningococcal meningitis remains a significant public health threat, especially in the African meningitis belt where Neisseria meningitidis serogroup A historically caused large-scale epidemics. With the rollout of a novel meningococcal serogroup A conjugate vaccine (MACV) in the belt, the World Health Organization recommended case-based meningitis surveillance to monitor MACV impact and meningitis epidemiology. In 2014, the MenAfriNet consortium was established to support strategic implementation of case-based meningitis surveillance in 5 key countries: Burkina Faso, Chad, Mali, Niger, and Togo. MenAfriNet aimed to develop a high-quality surveillance network using standardized laboratory and data collection protocols, develop sustainable systems for data management and analysis to monitor MACV impact, and leverage the surveillance platform to perform special studies. We describe the MenAfriNet consortium, its history, strategy, implementation, accomplishments, and challenges.